Transformasi Digital dalam Pelayanan Publik: Analisis Tantangan dan Strategi Inovasi Pelayanan Pencatatan Sipil di Era Digitalisasi: (Studi Kasus Penerbitan Akta Kelahiran di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo) - Wawan Sugianto; Amirul Mustofah; Eny Haryati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research analyses the challenges to service innovation in civil registration, specifically the issuance of birth certificates at the Sidoarjo Regency Department of Population and Civil Registration, within the context of governmental digital transformation. Employing a qualitative approach via in-depth interviews, field observations, and document analysis, the study identifies various obstacles encountered in the process of public service digitisation. The findings indicate that the principal challenges include: (1) resistance to change from both civil servants and the public regarding the digital system; (2) limitations in information technology infrastructure and internet connectivity in rural areas; (3) the digital literacy gap between urban and rural community groups; (4) the complexity of coordination among government agencies within the integrated system; and (5) budgetary constraints for continuous system maintenance and development. The study also found that despite various innovations such as online services, mobile apps, and digital queuing systems, their implementation still faces significant technical and non-technical impediments. These findings contribute to the literature on public sector innovation by revealing the dynamics of e-government implementation at the regency/city level, and offer strategic recommendations for policymakers on optimising the digital transformation of civil registration services. The novelty of this research lies in its comprehensive analysis, which integrates technological, organisational, and social perspectives within the context of local government in Indonesia post-COVID-19 pandemic.